Natural-Derived Polysaccharides From Plants, Mushrooms, and Seaweeds for the Treatment of Inflammatory Bowel Disease - Li, Cailan; Wu, Guosong; Zhao, Hualang; Dong, Na; Wu, Bowen; Chen, Yujia; Lu, Qiang (Frontiers in Pharmacology, 2021)
Inflammatory bowel disease (IBD) is a chronic inflammatory disease impairing the gastrointestinal tract, and its incidence and prevalence have been increasing over time worldwide. IBD greatly reduces peoples' quality of life and results in several life-threatening complications, including polyp, toxic colonic dilatation, intestinal perforation, gastrointestinal bleeding and cancerization. The current therapies for IBD mainly include drugs for non-critical patients and operation for critical patients. However, continuous use of these drugs causes serious side effects and increased drug resistance, and the demand of effective and affordable drugs with minimal side effects for IBD sufferers is urgent. Natural-derived polysaccharides are becoming a research hotspot for their therapeutic effects on IBD. This paper focuses on the research progress of various natural polysaccharides from plants, seaweeds and mushrooms for the treatment of IBD during recent 20 years. Regulation of oxidative stress, inflammatory status, gut microbiota and immune system and protection of the intestinal epithelial barrier function are the underlying mechanisms for the natural-derived polysaccharides to treat IBD. The excellent efficacy and safety of polysaccharides, make them promising candidates for IBD therapy.